Herremændene i Jyske Lov - Ulsig, Erik (Historisk Tidsskrift, 2013)
"Herremænd" in the Danish Law of JutlandThe earliest mention of the Danish word herremand (pl. herremænd) appears in the 1241 Jyske Lov (Law of Jutland), III 7-20, in the chapters dealing with the naval levy (leding). The King, the Duke and the King's other children or kin as well as the bishops were entitled to accept fully armoured men for war duty and in return these were exempted from the levy tax. Jyske Lov gives the impression that herremænd were not very wealthy. To gain tax exemption they might, e.g., have to rent land, as long as it amounted to no more than a good peasant holding. Later in the thirteenth century recruitment rules led to conflicts among the mighty of the realm, especially conflicts between the King and the Archbishop, who were also in disagreement as to the right of disposal of the Archbishop's men in wartime. In Saxo's description of the Civil War (1146-57) and the Scandia Rebellion (1181-82) we meet two main social groups of combatants, magnates and milites (satellites). Magnates are known from various sources as rich and powerful men, while milites were men in the service of kings, princes or bishops. The word miles, however, was ambiguous. In Saxo and far into the thirteenth century it could also be used as a generic term for all combatants, but gradually it was limited to those who were knighted, thus designating only the most distinguished of the men of power. In the Late Middle Ages the word herremand appears again, but in a different meaning than in Jyske Lov. In a broad sense the term meant a man of rank or power, and when used precisely, it specifically denoted a nobleman. Here Herremand is a lord, whereas the herremand of Jyske Lov is a lord's man (homo domini). There are no arguments to support the idea of a gradual change of meaning, as was the case for the concept and word miles. The assumption, therefore, is that Jyske Lov exhibits a peculiar use of the word as a generic term for men serving under any of the many and various kinds of lords. Translated by Michael Wolfe